THE INNER CONFLICT OF SUICIDE PERFORMERS AND SOLUTION TO THE SUICIDE PROBLEMS IN YOGYAKARTA - Supadiyanto, Supadiyanto; Jamalullail, Jamalullail (An-Nida : Jurnal Komunikasi Islam, 2024)
Suicide cases in Indonesia are increasing from year to year. Suicide cases befell students in Yogyakarta, a major blow to the world of higher education. The formulation of the problem is, what is the model of inner conflict experienced by the perpetrators of student suicide in Yogyakarta? What is the solution to prevent and overcome cases of suicide experienced by students in Yogyakarta? This research paradigm is qualitative. Data collection techniques through focus group discussion (FGD), content analysis of news reports in the media, literature review, and observation. The research time is November 2023 to January 2024. Data analysis using the Miles and Huberman Model or Flow Model. The result is that suicide perpetrators experience inner conflict due to being hit by academic and/or non-academic problems. Romantic problems or failure to establish a love relationship, as well as difficulties in completing studies are the main causes of student suicide. The solution is that the campus detects the potential for student suicide earlier by establishing more intensive communication. Students must be more open and communicative with lecturers and other students. In another aspect, strengthening mental health, faith and devotion in students is important to prevent suicide. Revision of regulations regarding the prohibition of suicide is urgently implemented.